EMOSI DALAM KONSELING - Neni Noviza (Wardah, 2012)
Every human being must become acquainted with the issues, conflicts and situations / unpleasant occurrences associated with self, others and the environment. This is normal as a stage of life experiences and the development of a person. Therefore, we all must have experienced or have times when we are feeling down (sad, disappointed, discouraged, stress, depression, etc.) or even otherwise feel scared, anxious, overly excited and others. Many events in life that can not be avoided and that makes us feel things like the above. There are times when we can also solve the problem or feeling well but there are times when we feel stuck, confused, anxious, not knowing where to complain and think that no one can help. Counseling is one way to help solve a variety of problems in life. Counseling helps us to identify the problem, find a solution or an appropriate alternative and will realize the potential of every human being to be able to overcome its problems.